An REU in Glass Science – Lessons and Legacy for Undergraduate Materials Education. Issue 1762 (16th February 2015) - Heffner, William; Jain, Himanshu
ABSTRACT: Two important goals of the International Materials Institute for New Functionality in Glass (IMI-NFG) have been: (a) to facilitate international collaboration in glass research and, (b) to support the training of a professional workforce [1]. The REU program has been an important component of its mission since 2005. Glass science provides the central theme of our program, which has both an international and domestic component. In this paper we provide a summary of our accomplishments and experiences with this innovative, materials focused, multidisciplinary REU program. While glass provides the unifying theme of our program, the research topics and project advisers come from various departments, including not only materials science and engineering, but also biology, physics, environmental and civil engineering, electrical engineering, etc. This mode of REU operation has provided an effective means to introduce faculty from other departments to new, interdisciplinary applications of glass as an enabling material for their own work. For the domestic REU, we partner with the Physics REU Program at Lehigh, sharing many crucial administrative aspects including housing, seminars and social events. The complementary approach of the two REU programs has been very beneficial to both of them. We summarize approaches to recruitment, selection and creating an environment conducive to cohesive and motivated community of young researchers. While the majority of student experiences have been through individual projects, we have also experimented with small teams headed by a single adviser. Because the teams can exploit the combined strengths of its members, they can accommodate a greater diversity of individual student skills and experiences. Such projects tend to provide opportunity for open-ended exploration within the context of a general goal. Some of the projects are specifically focused on developing low-cost, hands-on demonstrations for teaching glass science to others through a more experiential and intuitive approach. All of these REU projects have been incorporated in an on-line collection of activities for the science education community at large, as reported previously [2, 3]. For the international component of REU, we have supported glass faculty in the country, who wish to engage their undergraduate students in a glass based summer research in the lab of an international colleague. These experiences require considerable preparation and individual attention. Here we discuss the challenges and successful strategies to deal with both the international and domestic programs.